Understanding World Christianity : Eastern Africa - Kollman, Paul V.; Smedley, Cynthia Toms, 1975- (Understanding world Christianity series., 2018)
Each volume of the Understanding World Christianity series analyzes the state of Christianity from six different angles. The focus is always Christianity, but it is approached in an interdisciplinary manner--chronological, denominational, sociopolitical, geographical, biographical, and theological. Short, engaging chapters help readers understand the complexity of Christianity in the region and broaden their understanding of the region itself. Readers will understand the interplay of Christianity and culture and will see how geography, borders, economics, and other factors influence Christian faith. In this exciting volume, Paul Kollman and Cynthia Toms Smedley offer an introduction to Eastern African Christianity that has been desperately needed by scholars, students, and interested readers alike. Rich in experience and knowledge, Kollman and Toms Smedley introduce readers to the vibrancy of Eastern African Christianity like no other authors have done before.